Analisis Pengaruh Kebijakan Dividen, Ukuran Perusahaan dan Keputusan Investasi terhadap Nilai Perusahaan pada Perusahaan Sektor Industri yang Terdaftar di BEI Periode 2020-2024 - Lilis Natalia; Juanda Astarani; Sari Rusmita (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze the effect of dividend policy, company size, and investment decisions on company value in the industrial sector listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. Company value is proxied using the Price to Book Value (PBV) ratio. Meanwhile, dividend policy is measured through the Dividend Payout Ratio (DPR), company size is represented by the natural logarithm of total assets (Ln Total Assets), and investment decisions are measured by the Price Earnings Ratio (PER). The research method applied is quantitative with a descriptive associative approach. Purposive sampling was used, resulting in 60 observations from 12 industrial companies during the five-year research period. Data analysis was performed using multiple linear regression techniques with statistical software. The findings reveal that, partially, dividend policy and investment decisions do not have a significant effect on company value. On the other hand, company size has a significant effect. Simultaneously, the three independent variables together showed a significant effect on company value. The implications of these results are expected to be a strategic consideration for company management and investors in their efforts to increase company value.